Eksistensi Homeless Media di Era Digital: Analisis Konten pada Akun Makassar Info - Ardyta Praviasari; Nur Annisa Fitri Syahrir (JURNALISTIK DAN MEDIA, 2025)
This study aims to examine the existence of homeless media in the digital era as reflected through the content shared by the Instagram account Makassar Info. This research employs a descriptive qualitative approach with a content analysis method. Theoretical frameworks used include content analysis theory to examine message characteristics and citizen journalism theory to understand the role of public participation in shaping media existence. The findings reveal that Makassar Info demonstrates a strong existence as a homeless media, despite not having a formal editorial structure. The account performs mass media functions through informative, educational, and participatory content. The content analysis indicates that the messages posted by Makassar Info represent the values and social functions of alternative media that contribute to local public communication. Therefore, the presence of Makassar Info illustrates a new form of citizen journalism in the digital space and proves that non-formal media can still function effectively within the modern communication system.